VHDL : modular design and synthesis of cores and systems. - Navabi, Zainalabedin, ....- (New York : McGraw-Hill, 2007)
Chapter 1: Digital System Design Automation with VHDL Chapter 2: RTL with VHDL Chapter 3: VHDL Constructs for Structure and Hierarchy Descriptions Chapter 4: Concurrent Constructs for RT Level Descriptions Chapter 5: Sequential Constructs for RT Level Descriptions Chapter 6: VHDL Language Utilities and Packages Chapter 7: VHDL Signal Model Chapter 8: Hardware Cores and Models Chapter 9: Core Design and Testability Chapter 10: Design, Test and Application of a Processor Core APPENDIX A: VHDL KEYWORDS APPENDIX B: VHDL LANGUAGE GRAMMAR APPENDIX C: VHDL STANDARD PACKAGES APPENDIX D: STD_LOGIC_1164 Package APPENDIX E: STD_LOGIC_TEXTIO Package APPENDIX F: STD_LOGIC_ARITH Package APPENDIX G: STD_LOGIC_SIGNED APPENDIX H: STD_LOGIC_UNSIGNED APPENDIX I: math_real Package
Keywords: VHDL (vhsic hardware description language).